PENGARUH NILAI TUKAR RUPIAH, FOREIGN DIRECT INVESTMENT (FDI), PINJAMAN LUAR NEGERI DAN NET EKPOR TERHADAP CADANGAN DEVISA DI INDONESIA TAHUN 2005-2019 - Anisa Febri; Syapsan Syapsan; Widayatsari Any (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of the influence of the rupiah exchange rate, foreign direct investment (FDI), foreign loans and net exports on foreign exchange reserves in Indonesia in 2005-2019. The data used is time series data for the period 2005-2019. This study uses the Multiple Linear Regression analysis method using the statistical program Eviews 10. This study provides partial results that the rupiah exchange rate has a negative and significant effect on foreign exchange reserves. Foreign direct investment (FDI) partially has a positive and insignificant effect on foreign exchange reserves. Partial foreign loans have a positive and significant effect on foreign exchange reserves. Net exports partially have a negative and insignificant effect on foreign exchange reserves. Simultaneously, the exchange rate, foreign direct investment (FDI), foreign loans and net exports together have a significant effect on foreign exchange reserves in Indonesia. The Adjusted R-Squared value in this study is 0.905239, which means that 91 percent of the foreign exchange reserve variable can be explained by the independent variables in this study, the remaining 9 percent is explained by other variables outside the research model. Keywords: Rupiah Exchange Rate, Foreign Direct Investment (FDI), Foreign Loans, Net Exports, Foreign Exchange Reserves